Retooling the Aging Health Workforce: A Phenomenological Study of Older Nurse Educators’ Digital Training and Productivity Needs - Queenever T. Blase; Carolina B. Tadlas (Qualitative and Quantitative Research Center, 2026)
The rapid digitization of higher education introduces operational complexities for the aging academic workforce, particularly within the tactile domain of nursing education. This descriptive phenomenological study explored the authentic lived experiences of older adult nurse educators navigating learning management systems within private higher education institutions, mapping their digital training and productivity needs. Guided by the COREQ guidelines, purposive sampling selected six informants aged 60 to 72 years with up to 20 years of academic tenure in Cebu City, Philippines. In-depth, semi-structured face-to-face interviews were evaluated using Colaizzi’s seven-step phenomenological approach, achieving data saturation at 100% code duplication. Five definitive themes emerged: overwhelming immediate exposure to varied digital tools, a sense of vulnerability and powerlessness, convenience in information exchange, adverse online teaching-learning encounters, and a proactive plea to meet productivity needs. The findings reveal a technological paradox where the administrative convenience of instant data exchange is deeply compromised by severe technostress, operational dependency, and pedagogical erosion during virtual clinical psychomotor evaluations. This inquiry concludes that technological vulnerability is a structural consequence of non-age-friendly environments rather than individual incompetence. Consequently, higher education administrators must transition from uniform technology mandates toward age-friendly human resource policies, incorporating structured reverse mentoring, dedicated instructional design support, and real-time helpdesks to optimize faculty retention, restore professional self-efficacy, and safeguard downstream patient safety.